Adobe Illustrator software in the development of student creativity - Abanto Vargas, Juan (2017)
The present work of research denominated "Adobe Illustrator Software in the development of the Creativity in the area of Education for the work in the students of the Second Degree" D "of the Educational Institution" José Gálvez "of the Province of Cajabamba, 2015"; Has the purpose of strengthening the creative capacity of students through graphic design and be themselves the protagonists of their learning. The objective of this research is to determine the influence of Adobe Illustrator Software in the development of students' creativity. The type of investigation corresponds to an explanatory application study and the research design Pre experimental. The population was made up of one hundred and sixty-two second-grade students, from which a probabilistic sample was chosen, consisting of thirty-three of the "D" section, demonstrating that the effectiveness of the Software studied has a great relevance in the development of the Abilities of the students, since it allows to express the ideas through a graphic design be it a logo, poster or any means of printed communication because it has a wide range of tools and options.